Pengaruh Citra Merek, Persepsi Harga dan Kualitas Produk Honda Brio Satya Terhadap Minat Beli Pelanggan di Jakarta - Dimas Rizky; Carunia Mulya Firdausy (Jurnal Manajemen Bisnis dan Kewirausahaan, 2020)
The purpose of this study is to examine the effects of brand image, perceive price and product quality on purchase intention. The number of sample in this study was 160 respondents consisting of potential customers and the customers Honda Brio Satya of PT. Honda Prospect Motor in Jakarta. The technique to sampling unit analysis was convenience nonprobality sampling method. The results of this study as follow. First, it was found that brand image has a positive and significant effect on purchase intention. Second, perceive price has a positive and significant effect on purchase intention. Third, product quality has a positive effect on purchase intention. Fourth, brand image, price perception and product quality jointlyl effect purchase intention of Honda Brio customer. Therefore, to improve the purchase intention of the customers, the company should give a great concern to brand image, price and the quality of Honda car production.